Costimulation blockade: current perspectives and implications for therapy. - Kinnear, G; Jones, N; Wood, K (2013)
T cells must be activated before they can elicit damage to allografts, through interaction of their T cell receptor (TCR) with peptide-MHC complex and through accessory molecules. Signaling through accessory molecules or costimulatory molecules is a critical way for the immune system to fine tune T cell activation. An emerging therapeutic strategy is to target selective molecules involved in the process of T cell activation using biologic agents, which do not impact TCR signaling, thus only manipulating the T cells, which recognize alloantigen. Costimulatory receptors and their ligands are attractive targets for this strategy and could be used both to prevent acute graft rejection as well as for maintenance immunosuppression. Therapeutic agents targeting costimulatory molecules, notably belatacept, have made the progression from the bench, through nonhuman primate studies and into the clinic. This overview describes some of the most common costimulatory molecules, their role in T cell activation, and the development of reagents, which target these pathways and their efficacy in transplantation.